BIOCONTROLED THERAPY IN THE HOLISTIC TREATMENT OF AUTOINFECTIOUS STOMATITIS - E. V. Nikolishyna; N. M. Ilenko; N. V. Ilenko (Ukrainian Medical Stomatological Academy, 2017)
The human body constantly works to maintain a state balance and close interrelation with different microorganisms. In their effects on the human body all microorganisms are divided into three groups: probiotic (98%); opportunistic (2%); pathogenic. If oral microflora disorder takes place, the number of probiotic microorganisms is quickly reduced, and the difference is replaced with opportunistic microflora, which can lead to autoinfectious stomatitis. The treatment of autoinfectious stomatitis is mainly focused on total pharmacological sterilization of the areas that contain bacteria using antibacterial drugs. Disregard for the ways how macro- and microorganisms interact leads to the emergence of resistant pathogen forms, formation of insufficient mechanisms for effective protection and/or development of dysbiosis. The goal of our work was to analyze modern drug groups that are used for bioregulatory therapy and their significance in autoinfectious stomatitis treatment. There were 48 patients with autoinfectious stomatitis under our surveillance. Each patient was provided with comprehensive examination: clinical (survey and inspection) and laboratory (general blood analysis, a swab or scraping from the oral mucous membrane for microscopic examination). The treatment control was performed not earlier than one month after the end of the treatment. Scientific studies undertaken in our department and years of observation experience of such patients allowed us to develop a scheme for bioregulatory therapy in complex autoinfectious stomatitis treatment. For localized treatment we recommend the use of the drug "Lysobact". The composition of this product contains lysozyme and pyridoxine. Lysozyme has bifidogenic, immunomodulatory, anti-inflammatory effects. It stimulates metabolic and reparative processes and increases mucous membranes resistance. It acts as an antibacterial agent against gram-positive pathogenic and opportunistic bacteria, including fungi and viruses. Pyridoxine provides a good protective effect on the oral mucous membrane. The drug "Yogurt" was recommended to ingest per os. The main pharmacodynamic role of this drug is achieved through different types of lactic acid bacteria contained in it. These bacteria are a part of regular oral microflora. Lactobacilli form antagonistic substances for pathogenic bacteria, enhance phagocytosis and are involved in immunoglobulin synthesis. Their protective abilities are aimed to control the growth of Staphylococcus, protozoan and fungal infection. These bacteria affect the overall acid-base balance, secreting lactic acid and lysozyme. During treatment, all patients in the experimental group noted positive dynamics in their condition. 11 patients (78,5%) with acute ulcerative gingivitis/stomatitis and acute aphthous stomatitis revealed the best positive dynamics in microbiological examination results. In all patients' smears actinomycetes, ameba bukalis, leptothrix and other forms of protozoa were absent. Thus, the application of bioregulatory therapy during complex treatment of patients with autoinfectious stomatitis leads not only to clinical symptoms elimination of the disease, but also to the overall restoration of the oral cavity microbiocenosis.